Urgensi Indonesia Untuk Meratifikasi Konvensi Tentang Perlindungan Terhadap Penghilangan Orang Secara Paksa - Nurul Fitrah; Arman Anwar; Irma Halima Hanafi (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Special Committee of the House of Representatives on the Handling of Discussions on the Results of the Investigation into the Enforced Disappearance of Persons for the Period 1997-1998, has issued four points of recommendation to the President. One of the four points is to urge the government to immediately ratify the convention on protection against forced disappearances of persons.Purposes of the Research: The purpose of this research was to determine the regulation of international law against forced disappearances of persons, and to know the urgency of Indonesia to ratify the convention on the protection against forced disappearances of persons. Methods of the Research: The research methods used are normative juridical research methods, analytical descriptive research types, sources of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Technical collection of legal materials through library research and processing techniques for legal materials using qualitative analysis.Results of the Research: The result of the study is that international convention for the protection of all persons from enforced disappearance is an international instrument that regulates the obligations and responsibilities of states in providing protection to all persons from enforced disappearances. Indonesia has not yet ratified the convention of the protection of all persons from enforced disappearances. This Convention is very urgent to be ratified by Indonesia because it is one of the foundations of international human rights law that can provide protection, as well as a preventive and corrective effort of the state in ensuring the protection of all people from enforced disappearances. In addition, it is also to encourage cases of enforced disappearances in Indonesia in the past to be resolved and not repeated in the future.